Removal of phenol from wastewater using Luffa cylindrica fibers in a packed bed column: Optimization, isotherm and kinetic studies - Samuel Ogunniyi; Ebuka Chizitere Emenike; Kingsley O. Iwuozor; Joshua O. Ighalo; Abdelrahman O. Ezzat; Tunmise Latifat Adewoye; Abel Egbemhenghe; Hussein K. Okoro; Adewale George Adeniyi (Heliyon, 2024)
This research entails a comparison of the effectiveness of unmodified Luffa cylindrica fiber in a fully packed bed (RLCF) and NaOH-modified Luffa cylindrica fiber in another fully packed bed (MLCF) in the context of phenol removal from wastewater. Experimental data obtained through batch adsorption experiments were utilized to determine the most suitable model. It was observed that as the initial concentration of phenol increased from 100 to 500 mg/l, the maximum percentage removal increased from 63.5 to 83.1% for RLCF-PB and from 89.9 to 99.5% for MLCF-PB. The correlation coefficient (R2) was calculated for the Langmuir, Freundlich, Temkin, Harkin-Jura, Halsey, and Flory-Huggins models for both materials. The analysis revealed that the pseudo-second-order model was the most suitable, followed by the Elovich model, with the pseudo-first-order model being the least suitable. The Weber-Morris diffusion model suggested that pore diffusion was the rate-determining step, and diffusion at the border layer was determined to be endothermic, feasible, heterogeneous, and spontaneous. In summary, this study indicates that MLCF-PB is a promising material for the efficient removal of phenol from aqueous solutions.